A randomized control trial of meditation compared to music listening to improve cognitive function for breast cancer survivors: Feasibility and acceptability. (November 2020) - Henneghan, Ashley M.; Becker, Heather; Harrison, Michelle L.; Inselmann, Kelly; Fico, Brandon; Schafer, Helen; King, Elisabeth; Patt, Debra; Kesler, Shelli
Abstract: Background: and Purpose: Many breast cancer survivors (BCS) experience persistent cognitive and psychological changes associated with their cancer and/or treatment and that have limited treatment options. Therefore, the purpose of this study was to explore the feasibility and effects of a Kirtan Kriya meditation (KK) intervention on cognitive and psychological symptoms compared to an attention control condition, classical music listening (ML), in BCS. Materials and methods: A randomized control trial design was used. Participants completed eight-week interventions. Cognitive function and psychological symptoms were measured at baseline and post-intervention. Mixed analysis of variance models were examined for all cognitive and psychological outcomes. Results: 27 BCS completed the study. Intervention adherence was 88%. Both groups improved in perceived cognitive impairments, cognition related quality of life, verbal memory, and verbal fluency ( p's  < 0.01). There were no significant group by time effects for cognitive and psychological outcomes, except stress. The ML group reported lower stress at time 2 ( p  < 0.05). Conclusion: KK and ML are feasible, acceptable, and cost-effective interventions that may be beneficial for survivors' cognition and psychological symptoms. Both interventions were easy to learn, low cost, and required just 12 min/day. Meditation or music listening could offer providers evidence-based suggestions to BCS experiencing cognitive symptoms. Clinical trials registration number: NCT03696056. Highlights: Delivery of a remote 8-week, 12 min/day meditation and music interventions to breast cancer survivors is feasible. Kirtan Kriya meditation may improve verbal fluency and memory, perceived cognitive functioning, and quality of life. Music listening may improve verbal fluency and memory, perceived cognitive functioning, quality of life, and perceived stress.